Two-level method of hierarchical-coordination QoS routing based on resource reservation - Yeremenko, O.S. (Radiotekhnika, 2018)
A method of hierarchical-coordination QoS routing based on network resource reservation is proposed. The proposed method is based on the introduction of a two-level hierarchy of solutions. The lower level was responsible for ensuring a consistent solution of problems of the distributed source routing and reserving the link resource with the provision of end-to-end QoS requirements for the packet rate and average packet delay. The main task of the upper level is overload preventing of communication links during the reservation of their bandwidth initialized in distributed manner by each of the border routers of the network. It is established that the method provides an iterative calculation of the required control variables; the number of such iterations depended on the network structure, the amount of available network resources, the number of flows and their QoS requirements.